An organization on the edge of chaos: the origins of the metaphor and its impact on the theory and practice of strategic management - Mesjasz, Czesław (Wpływ metafory „organizacja na krawędzi chaosu” na teorię i praktykę zarządzania strategicznego, 2019)
The notion “edge of chaos” coined in complex systems studies has become a part of the vocabulary of modern management theory and practice. This utterance is especially significant since it has been applied in management as a metaphor associated with innovativeness and creativity. The aim of the paper is to study what are the consequences of the fact that this term is applied in management as a dead metaphor, i.e. it is decoupled from its initial meaning. A deepened analysis of the interpretations and misinterpretations of the term “organization on the edge of chaos” applied in strategic management is presented
Management Sciences = Nauki o Zarządzaniu, 2019, vol. 24, no. 2, s. 3-8
Keywords: organization on the edge of chaos; dead metaphor; strategic management; organizacja na krawędzi chaosu; martwa metafora; zarządzanie strategiczne